2008
DOI: 10.1111/j.1469-1809.2008.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Association of Common AGGF1 Variants with Susceptibility for Klippel‐Trenaunay Syndrome Using the Structure Association Program

Abstract: SummaryKlippel-Trenaunay syndrome (KTS) is a severe congenital disorder characterized by capillary malformations, venous malformations or varicose veins, and hypertrophy of the affected tissues. The angiogenic factor gene AGGF1 was previously identified as a candidate susceptibility gene for KTS, but further genetic studies are needed to firmly establish the genetic relationship between AGGF1 and KTS. We analyzed HapMap data and identified two tagSNPs, rs13155212 and rs7704267 that capture information for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 30 publications
0
43
0
4
Order By: Relevance
“…Tissue immunostaining studies with an anti-AGGF1 antibody identified strong AGGF1 protein expression in blood * This study was supported in part by a Scott Hamilton CARES research grant vessels embedded in various tissues including the heart, kidney, tail, and limb and co-localized with an endothelial specific marker CD31 as well as a vascular smooth muscle cell-specific marker, smooth muscle cell ␣-actin (1). In a small case control study, the frequency of a single nucleotide polymorphism (SNP) in AGGF1, E133K, was found to be greater in cases (3.8%) than in controls (1), but later studies found that E133K showed a frequency of 2.2-3.3% in other general control populations (6,11,12). These results argue that SNP E133K is unlikely to confer a risk of KTS.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Tissue immunostaining studies with an anti-AGGF1 antibody identified strong AGGF1 protein expression in blood * This study was supported in part by a Scott Hamilton CARES research grant vessels embedded in various tissues including the heart, kidney, tail, and limb and co-localized with an endothelial specific marker CD31 as well as a vascular smooth muscle cell-specific marker, smooth muscle cell ␣-actin (1). In a small case control study, the frequency of a single nucleotide polymorphism (SNP) in AGGF1, E133K, was found to be greater in cases (3.8%) than in controls (1), but later studies found that E133K showed a frequency of 2.2-3.3% in other general control populations (6,11,12). These results argue that SNP E133K is unlikely to confer a risk of KTS.…”
mentioning
confidence: 96%
“…KTS is a congenital disorder, but most cases are sporadic. The genetic basis of KTS is complex and may involve multiple genes, environmental factors, and their interactions (6). To date, identification of susceptibility genes associated with KTS has relied upon gross cytogenetic defects reported in KTS patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,15,16 Aggf1 encodes an interesting angiogenic factor with G-Patch and FHA domains and is associated with increased susceptibility for the vascular disease Klippel-Trenaunay syndrome. [27][28][29] Similar to the vascular endothelial growth factor (VEGF) A, purified wild-type AGGF1 protein promoted strong angiogenesis. 27 Recently, we demonstrated that aggf1 plays an important role in the specification of veins and angiogenesis by activating the AKT signaling pathway in zebrafish embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…3:q13) has also been reported (Wang et al, 2001). (8) Most cases of KTS are sporadic. But there are certain cases reported which suggests an autosomal dominant pattern of inheritance.…”
Section: Case Reportmentioning
confidence: 99%